High-temperature oxidation resistant gradient coating and preparation method thereof

By forming a gradient structure of nickel-plating layer, nano-adhesive layer and high-entropy alloy layer on the surface of the titanium alloy, combined with cold spraying and oxyacetylene flame treatment, the problem of poor adhesion of titanium alloy coating at high temperatures is solved, and high efficiency is achieved The antioxidant properties and adhesion are improved, extending the life of the equipment.

CN119162575AActive Publication Date: 2024-12-20SHANGHAI UNIV +1

Patent Information

Application Number
CN202411186870.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-28
Publication Date
2024-12-20
Estimated Expiration
2044-08-28

AI Technical Summary

Technical Problem

The existing high-temperature oxidation gradient coatings of existing titanium alloys have problems of poor adhesion and insufficient strength in practical applications, which limit their performance in high-temperature environments.

Method used

The gradient structure of nickel plating layer, nano bonding layer and multi-layer high entropy alloy layer is adopted. Through electroplating nickel layer, cold spraying process and oxyacetylene flame semi-melt-curing treatment, combined with vacuum sintering process, it forms excellent resistance to high temperature oxidation. Coatings of properties and adhesion.

Benefits of technology

It significantly improves the oxidation resistance and adhesion of titanium alloy in high temperature environments, extends the service life of the equipment, and enhances the hardness and wear resistance of the coating through ceramic nano Al2O3 particles, and reduces mechanical friction and wear.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119162575A_ABST
    Figure CN119162575A_ABST
Patent Text Reader

Abstract

The invention discloses a high-temperature oxidation resistant gradient coating and a preparation method thereof, and belongs to the field of coating preparation. The coating comprises a nickel plating layer, a nano adhesive layer and a working layer which are sequentially arranged from inside to outside. The method comprises the following steps that firstly, a titanium alloy base material is prepared, and base material pretreatment is conducted; 2, electroplating a nickel layer on the titanium alloy base material; 3, spraying a nano adhesive layer on the nickel plating layer; 4, spraying high-entropy alloy powder on the nano adhesive layer to form a base layer; 5, adhesive removal and semi-melting-curing treatment are conducted on the base coat; sixthly, a nanometer adhesive and high-entropy alloy powder are circularly and cold sprayed on the base layer layer by layer till a working layer is formed; 7, vacuum sintering; and 8, after the vacuum sintering is finished, slowly cooling to room temperature to finish the preparation of the coating. The gradient coating with excellent high-temperature oxidation resistance and adhesive force can be prepared by redesigning the structure of the coating and matching with a unique preparation process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of coating preparation, and more specifically, relates to a high-temperature oxidation resistant gradient coating and a preparation method thereof. Background Art

[0002] As a key structural material in the aerospace field, titanium alloy has the advantages of low density, high specific strength, and excellent corrosion resistance. Among them, heat-resistant titanium alloy can form a dense oxide film at high temperature, blocking oxygen penetration and improving oxidation resistance. It is widely used in high-temperature components such as aircraft engines, turbine blades, and combustion chambers. However, when the temperature exceeds 500°C, titanium alloy is very prone to "oxygen embrittlement" damage, resulting in a serious decline in mechanical properties and even the "titanium fire" phenomenon, which has become the main bottleneck restricting the high-temperature application of titanium alloys. Since high-temperature oxidation mainly occurs on the surface of titanium alloys, preparing an excellent high-temperature oxidation-resistant coating on its surface is considered to be the most effective way to improve the high-temperature service performance of titanium alloys. In response to this problem, the existing technology has also made some research on improving the performance of the coating.

[0003] As a new type of coating material, high entropy alloy has become a hot topic of research due to its excellent high-temperature oxidation resistance, wear resistance and chemical stability. Zhang Xiaoxian et al. [Zhang Xiaoxian, Jie Fang, Zhai Changsheng, et al. Effect of induction coating temperature on the high-temperature oxidation resistance of FeCoCrNiMoBSi high entropy alloy coating [J]. Heat Treatment of Metals, 2023, 48(6): 52-58] prepared three types of FeCoCrNiMoBSi high entropy alloy coatings on 15CrMo steel substrate by flame thermal spraying combined with induction coating. The results show that after oxidation at 900℃ for 120h, the oxidation mass increases of the above three coatings are 0.58, 0.50 and 0.54 mg / cm, respectively. 2 , while the oxidation mass increase of the matrix is ​​73.28 mg / cm 2 , which is about 146 times the increase in coating oxidation mass. This shows that high entropy alloy coatings have significant oxidation resistance at high temperatures. However, flame thermal spraying technology has problems such as heat-affected zone, high-temperature oxidation, coating quality and thickness control during application, which limits its use in some cases.

[0004] Another example is a Chinese patent application number: CN202111250907.X, published on January 28, 2022, which discloses a Cr for titanium alloy. 2 O 3 / Al 2 O 3 Gradient anti-oxidation coating and preparation method thereof, the method adopts magnetron sputtering method to sputter-plate Cr metal layer on the surface of titanium alloy, then covers aluminum foil and melts the aluminum foil through high temperature heat treatment, finally forming Cr 2 O3 / Al 2 O 3 However, although this coating is also a gradient coating for titanium alloy, its bonding only relies on the high-temperature melting of aluminum foil. The adhesion between the gradient coatings in actual preparation is not high, and the coating strength will also be affected.

[0005] In summary, although the existing technology has made some progress in improving the high-temperature oxidation resistance of titanium alloys, there are still some problems in practical applications. Therefore, it is of great practical significance to study and develop new coating materials and preparation processes to further improve the high-temperature service performance of titanium alloys. Summary of the invention

[0006] 1. Problems to be solved

[0007] In view of the fact that the existing high-temperature oxidation resistant gradient coatings for titanium alloys still have certain problems in practical applications, the present invention provides a high-temperature oxidation resistant gradient coating and a preparation method thereof. By redesigning the structure of the coating and combining it with a unique preparation process, a gradient coating with excellent high-temperature oxidation resistance and adhesion can be prepared.

[0008] 2. Technical solution

[0009] To solve the above problems, the present invention adopts the following technical solutions.

[0010] A high temperature oxidation resistant gradient coating, comprising a nickel plating layer, a nano adhesive layer and a working layer arranged sequentially from inside to outside;

[0011] The chemical composition and mass percentage of the nickel plating layer are: nickel: 98-99%, sulfur: 0.01-0.05%, and the balance is other impurity elements;

[0012] The chemical composition and mass percentage of the nano adhesive layer are: polyvinyl alcohol: 50-70%, plasticizer: 5-10%, ceramic nano Al 2 O 3 Particles: 10-20%, deionized water: 10-20%;

[0013] The working layer comprises a plurality of high entropy alloy layers, wherein a nano adhesive is provided between two adjacent high entropy alloy layers, and the chemical composition and mass percentage of the high entropy alloy layers are as follows: carbon: 0.1-0.5%, boron: 1-1.3%, chromium: 19-21%, nickel: 21-24%, silicon: 1-1.5%, molybdenum: 8-10%, cobalt: 22-24%, sulfur: 0.005-0.015%, phosphorus: 0.015-0.045%, and the remainder is iron and unavoidable impurities.

[0014] As a further improvement of the technical solution, the thickness of the nickel plating layer is 30 to 50 μm.

[0015] As a further improvement of the technical solution, the thickness of the nano adhesive layer is 10 to 20 μm.

[0016] As a further improvement of the technical solution, the thickness of the high entropy alloy layer is 100-200 μm, and the thickness of the working layer is 1-1.2 mm.

[0017] A method for preparing a high temperature oxidation resistant gradient coating comprises the following steps:

[0018] 1. Prepare the titanium alloy substrate and perform ultrasonic cleaning and pickling activation treatment;

[0019] 2. electroplating a nickel layer on the titanium alloy substrate to form a nickel-plated layer;

[0020] 3. Spraying a nano adhesive layer on the nickel-plated layer using a cold spraying process;

[0021] Fourth, a cold spraying process is used to spray high entropy alloy powder on the nano adhesive layer to form a base layer;

[0022] 5. Use an oxyacetylene flame spray gun to remove the adhesive and semi-melt-solidify the primer layer;

[0023] 6. On the basis of the base layer, cold spray the nano adhesive and high entropy alloy powder layer by layer until a working layer is formed;

[0024] 7. Vacuum sintering the cold sprayed working layer;

[0025] 8. After the vacuum sintering is completed, slowly cool to room temperature to complete the coating preparation.

[0026] As a further improvement of the technical solution, in step 2, the nickel-plated layer is prepared by:

[0027] (1) Adding nickel sulfate, nickel chloride and boric acid into the electroplating tank, adjusting the pH value of the electroplating solution to 4 to 4.5, and heating the electroplating solution to 50 to 60° C.;

[0028] (2) Use high-purity nickel as the anode material for electroplating, with a current density of 2 to 4 A / dm 2 The electroplating time is 1 to 2 hours.

[0029] As a further improvement of the technical solution, in step three, the spraying pressure is 0.2-0.4 MPa, the nozzle diameter is 0.2-0.4 mm, the spraying distance is 10-20 cm, and the spraying speed is 100-200 mm / s.

[0030] As a further improvement of the technical solution, in step four, the spraying pressure is 1.5-3 MPa, the nozzle diameter is 0.8-1.2 mm, the spraying distance is 25-35 cm, and the spraying speed is 150-300 mm / s.

[0031] As a further improvement of the technical solution, in the step five, when the debonding treatment is performed, the flame temperature is 200-300°C, the nozzle diameter is 1.0-1.5 mm, the distance between the nozzle and the surface of the base layer is 10-15 cm, and the heating is performed for 5-10 seconds each time; when the semi-melting-curing treatment is performed, the flame temperature is 600-800°C, the nozzle diameter is 1.0-1.5 mm, the distance between the nozzle and the surface of the base layer is 10-20 cm, and the heating is performed for 5-10 seconds each time.

[0032] As a further improvement of the technical solution, in step seven, a step-by-step heating method is adopted, specifically:

[0033] (1) Heating from room temperature to 500°C at a rate of 10°C / min and keeping at 500°C for 30 min;

[0034] (2) heating from 500°C to 800°C at a rate of 10°C / min and maintaining at 800°C for 30 min;

[0035] (3) Raise the temperature from 800°C to 1200-1300°C at a rate of 5°C / min and keep at 1200-1300°C for 1-2 hours.

[0036] 3. Beneficial effects

[0037] Compared with the prior art, the present invention provides a high temperature oxidation resistant gradient coating and its preparation method, which adopts CoCrFeNiBSi high entropy alloy coating. The coating has excellent oxidation resistance in high temperature environment, can effectively prevent oxygen from penetrating into the coating, and is suitable for high temperature working environment. In addition, the ceramic nano-Al added in the nano-adhesive layer 2 O 3 The particles not only improve the hardness and wear resistance of the coating, but also fill the microscopic voids and pores in the coating, increase the density of the coating, and reduce the loss in mechanical friction and wear. At the same time, the use of electroplated nickel layer as a transition layer can effectively alleviate the difference in thermal expansion coefficient between the titanium alloy substrate and the high entropy alloy coating, reduce the stress and cracks caused by thermal expansion mismatch, provide a good base, and enhance the adhesion and high temperature stability of the coating.

[0038] Secondly, the present invention adopts oxyacetylene flame semi-melting-curing treatment, which can realize the metallurgical bonding of coating material and substrate, form a dense bonding layer, and significantly improve the adhesion and high temperature resistance of coating. At the same time, the cold spraying process is adopted to avoid the common thermal stress and heat-affected zone problems in the thermal spraying process, reduce the thermal damage and deformation of the substrate, improve the chemical purity and physical properties of the coating, and have high deposition efficiency and thickness control accuracy. The step-by-step vacuum sintering process gradually adapts the substrate and coating to the temperature change through slow heating and staged temperature control, avoiding the thermal stress concentration and material cracks caused by the rapid heating, and finally forming a uniform and dense structure, improving the comprehensive performance of the coating.

[0039] In particular, the present invention, through the combination of multiple processes and the design of the composition of the gradient coating, can prepare a gradient coating with excellent high-temperature oxidation resistance and adhesion under the cold spray process, significantly improve the oxidation resistance of titanium alloy in high temperature environment, and effectively extend its service life. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] Figure 1 This is a schematic diagram of the structure of the high-temperature oxidation resistant gradient coating on the surface of TC11 titanium alloy;

[0041] Figure 2 is the XRD pattern of FeCoCrNiMoBSi powder;

[0042] Figure 3 It is a structural schematic diagram of a device for electroplating nickel on the surface of a titanium alloy substrate;

[0043] Figure 4 It is the step temperature rise curve of vacuum sintering process;

[0044] Figure 5 It is a histogram of the microhardness of each coating in the embodiments and comparative examples;

[0045] Figure 6 It is a bar graph of the oxidation weight gain rate of each coating in the embodiments and comparative examples. DETAILED DESCRIPTION

[0046] Exemplary embodiments of the present invention are described in detail below. Although these exemplary embodiments are described in sufficient detail to enable those skilled in the art to implement the present invention, it should be understood that other embodiments may be implemented and various changes may be made to the present invention without departing from the spirit and scope of the present invention. The more detailed description of the embodiments of the present invention below is not intended to limit the scope of the claimed invention, but is merely for illustration and does not limit the description of the features and characteristics of the present invention, in order to propose the best mode for performing the present invention, and is sufficient to enable those skilled in the art to implement the present invention. Therefore, the scope of the present invention is limited only by the appended claims.

[0047] A high temperature oxidation resistant gradient coating can be applied to high temperature working environment in the aerospace field, can effectively improve the high temperature oxidation resistance and wear resistance of the coating, and prolong the service life of the equipment, and is particularly suitable for titanium alloy materials. The gradient coating is composed of a nickel plating layer, a nano adhesive layer and a working layer. The structural diagram of the gradient coating is shown in the figure. Figure 1 shown.

[0048] Among them, the chemical composition and mass percentage of the nickel plating layer are: nickel: 98-99%, sulfur: 0.01-0.05%, and the remainder is other impurities (such as hydrogen, oxygen, etc.); the nickel plating layer is a coating covering the surface of the titanium alloy substrate and bonded to the substrate, with a thickness of generally 30-50μm.

[0049] The chemical composition and mass percentage of the nano adhesive layer are: polyvinyl alcohol: 50-70%, plasticizer: 5-10%, glycerol is generally used, and ceramic nano Al is used as the filler. 2 O 3 Particles: 10-20%, deionized water: 10-20%. The nano adhesive is evenly sprayed on the surface of the nickel-plated layer using a cold spraying process, and the thickness is generally 10-20 μm.

[0050] The working layer includes multiple high entropy alloy layers, and there is a nano adhesive between two adjacent high entropy alloy layers. The chemical composition and mass percentage of the high entropy alloy layer are: carbon: 0.1-0.5%, boron: 1-1.3%, chromium: 19-21%, nickel: 21-24%, silicon: 1-1.5%, molybdenum: 8-10%, cobalt: 22-24%, sulfur: 0.005-0.015%, phosphorus: 0.015-0.045%, and the balance is iron and unavoidable impurities. The phase structure of the FeCoCrNiMoBSi powder is FCC, such as Figure 2 The high entropy alloy powder is uniformly sprayed on the nano adhesive layer by cold spraying process, the single layer thickness is generally 100-200 μm, and the nano adhesive and high entropy alloy powder are deposited to 1-1.2 mm by cold spraying layer by layer.

[0051] The above gradient coating uses an electroplated nickel layer as the bottom layer, and cold-sprays a nano-adhesive and a high-entropy alloy layer on the bottom layer layer by layer as the working layer. Its main raw material is CoCrFeNiMBSi high-entropy alloy, which has excellent oxidation resistance, corrosion resistance and wear resistance in high temperature environments, and the performance of the coating itself is guaranteed to a certain extent. 2 O 3The particles are not easy to decompose or react in high temperature environments, and can form a stable oxide film at high temperatures to prevent oxygen from penetrating into the coating, thereby further improving the high temperature stability and oxidation resistance of the coating, making it suitable for high temperature working environments in the aerospace field. 2 O 3 The particles have high hardness, which improves the hardness and wear resistance of the coating, can effectively reduce the loss of the coating in mechanical friction and wear, and extend the service life of the coating.

[0052] Secondly, the present invention performs a gradient treatment on the coating, and the nickel-plated layer serves as a transition layer, which can effectively alleviate the difference in thermal expansion coefficients and reduce the stress and cracks caused by thermal expansion mismatch in high temperature environments. The thermal expansion coefficient of nickel is between that of the titanium alloy and the coating material, which plays a role of buffering and transition. In addition, the nickel-plated layer provides a good substrate, which helps to enhance the adhesion of the subsequent high-entropy alloy coating. An oxide film is easily formed on the surface of the titanium alloy, and coating deposition directly thereon may result in poor adhesion. The electroplated Ni layer can effectively cover the surface of the titanium alloy, making it easier for the high-entropy alloy coating to adhere thereto evenly and firmly. The nickel-plated layer not only enhances the adhesion of the coating, but also nickel has good corrosion resistance, which can provide additional protection in high temperature and corrosive environments to prevent the titanium alloy substrate from being corroded.

[0053] The working layer is cold-sprayed with nano-adhesive and high-entropy alloy coating layer by layer. This layered structure design ensures the stability and durability of the coating in high temperature environment. The layered deposition controls the thickness and uniformity of each layer, effectively disperses thermal stress, avoids stress concentration and structural defects. In addition, the ceramic nano-Al in the nano-adhesive 2 O 3 The particles can fill the microscopic voids and pores in the coating, increase the density of the coating, and reduce the porosity of the coating. 2 O 3 The uniform distribution of particles can make the coating structure more uniform and avoid performance degradation caused by local defects. 2 O 3 Particles can play a toughening role in the coating, improving the toughness of the coating by refining the grains and preventing crack propagation.

[0054] The preparation method of the high temperature oxidation resistant gradient coating for titanium alloy comprises the following steps:

[0055] 1. Prepare a titanium alloy substrate for cold spraying, immerse the titanium alloy substrate in anhydrous ethanol solution for ultrasonic cleaning to remove oil and pollutants.

[0056] Second, immerse the cleaned titanium alloy substrate in an acid pickling solution for surface activation treatment as required to remove the surface oxide layer and expose the pure metal substrate, and then electroplate a nickel layer on the surface of the activated titanium alloy substrate to form a bottom coating. The preparation process of the electroplated nickel layer in this step is as follows: Figure 3 As shown, the following steps are included:

[0057] (1) Add nickel sulfate (NiSO 4 6H 2 O): 240~300g / L; Nickel chloride (NiCl 2 6H 2 O): 30~90g / L; Boric acid (H 3 BO 3 ): 30-45 g / L, use a glass rod or magnetic stirrer to stir thoroughly until all chemicals are completely dissolved. Use dilute sulfuric acid or sodium hydroxide to adjust the pH value of the plating solution to 4-4.5. Heat the plating solution to 50-60°C and maintain a constant temperature.

[0058] (2) Immerse the titanium alloy substrate in a pickling solution (HF 30-40 mL, HNO 3 70~80mL), the immersion time is controlled at 1~3 minutes. After activation treatment, the substrate is thoroughly rinsed with deionized water and blown dry to prepare for plating.

[0059] (3) Use high-purity nickel as the anode material to ensure that the anode can stably provide nickel ions. Clamp the surface-activated titanium alloy substrate on the electroplating rack, and place the titanium alloy substrate and the nickel anode in the electroplating tank respectively to ensure that the electroplating solution completely covers the substrate and the anode.

[0060] (4) Set the current density to 2-4A / dm 2 The electroplating time is generally controlled within 1 to 2 hours to ensure that the Ni layer thickness reaches 30 to 50 μm. During the electroplating process, the plating solution temperature and pH value are checked regularly to ensure that they are within the set range, and the plating solution is gently stirred with a glass rod to maintain uniform plating conditions.

[0061] (5) After the electroplating is completed, the titanium alloy substrate is taken out from the electroplating tank, and the substrate is thoroughly rinsed with deionized water to remove the electroplating solution residue. Finally, the substrate is placed in a constant temperature drying oven for drying to obtain a titanium alloy substrate with a nickel-plated layer on the surface.

[0062] 3. Prepare nano adhesive according to the set composition, use cold spray equipment, spray pressure: 0.2-0.4MPa, nozzle diameter: 0.2-0.4mm, spray distance: 10-20cm, spray speed: 100-200mm / s, spray the nano adhesive evenly on the surface of the electroplated nickel layer, and ensure that the single layer thickness is controlled at 10-20μm. Then use cold spray equipment, spray pressure: 1.5-3MPa, nozzle diameter: 0.8-1.2mm, spray distance: 25-35cm, spray speed: 150-300mm / s, directly cold spray the high entropy alloy powder on the nano adhesive layer, and evenly mix the high entropy alloy powder and the adhesive through high-speed impact to form a base layer. The first layer of the working layer is called the base layer.

[0063] Compared with the thermal spraying process, the cold spraying process for coating preparation not only avoids the common thermal stress and heat-affected zone problems in the thermal spraying process, but also reduces the thermal damage and deformation of the substrate. It also avoids the common oxidation and phase change problems in the high-temperature coating process, and the coating has better chemical purity and physical properties. In addition, the high-speed impact of cold spraying allows the powder particles to be firmly attached to the surface of the substrate, forming a high-density and high-bonding-strength coating with high deposition efficiency. The coating thickness can also be precisely controlled by adjusting the spraying parameters, which is suitable for preparing coatings from micron to millimeter level to meet different application requirements.

[0064] Fourth, use an oxyacetylene flame spray gun to remove the adhesive from the base layer in step 3, flame temperature: 200-300°C, flame type: neutral flame (equal ratio of oxygen and acetylene), nozzle diameter: 1.0-1.5mm, distance between nozzle and coating surface: 10-15cm, scan the surface of the base layer evenly and slowly, heat for 5-10 seconds each time, and gradually heat until the adhesive is completely volatilized. Then use an oxyacetylene flame spray gun to semi-melt-cured the base layer, flame temperature: 600-800°C, flame type: neutral flame (equal ratio of oxygen and acetylene), nozzle diameter: 1.0-1.5mm, distance between nozzle and coating surface: 10-20cm, scan the surface of the base layer evenly and slowly, heat for 5-10 seconds each time, and gradually heat until it reaches a semi-molten state. After stopping heating, cool under a protective atmosphere (such as nitrogen or argon).

[0065] The coating is debonded and semi-melted-cured by an oxyacetylene flame method. The oxyacetylene flame can efficiently remove the organic components in the nano-adhesive, ensure that there is no residual adhesive in the coating, and improve the purity and stability of the coating. In addition, the flame temperature is increased, and the coating is locally heated by the oxyacetylene flame to reach a semi-molten state. This means that some areas of the coating material melt, while some areas remain solid. In the semi-molten state, the metal atoms at the interface between the Ni-plated layer and the coating material and the titanium substrate begin to diffuse with each other to form a metallurgical bond. After the heating stops, the material cools rapidly, and the semi-molten area re-solidifies to form a dense and firm bonding layer, which enhances the density and adhesion of the coating. The semi-melted-curing treatment can achieve metallurgical bonding between the coating material and the substrate, forming a dense bonding layer, and significantly improving the adhesion and high temperature resistance of the coating.

[0066] 5. On the basis of the base layer, cold spray the nano adhesive and high entropy alloy powder layer by layer to ensure that the single layer thickness is controlled at 100-200 μm. In addition to the base layer, after each spraying, the coating is treated with an oxyacetylene flame spray gun for de-adhesive treatment and semi-melting-solidification until the cyclic deposition reaches a working layer of 1-1.2 mm.

[0067] The working layer is cold-sprayed with nano-adhesive and high-entropy alloy coating layer by layer. This layer-by-layer deposition controls the thickness and uniformity of each layer, ensuring the stability and consistency of the coating in a high-temperature environment. Layer-by-layer deposition helps to disperse thermal stress and avoid stress concentration and structural defects. In addition, the ceramic nano-Al in the nano-adhesive 2 O 3 The particles can fill the microscopic voids and pores in the coating, increase the density of the coating, and reduce the porosity of the coating. 2 O 3 The uniform distribution of particles can make the coating structure more uniform and avoid performance degradation caused by local defects. 2 O 3 Particles can play a toughening role in the coating, improving the toughness of the coating by refining the grains and preventing crack propagation.

[0068] 6. Vacuum sinter the cold sprayed working layer coating. Use a step-by-step heating method to slowly heat up to the sintering temperature, and keep it at the sintering temperature (1200-1300°C) for 1-2 hours to allow the coating material to fully diffuse and combine to form a uniform and dense structure. Finally, slowly cool it to room temperature in a vacuum furnace to complete the coating preparation. The step-by-step heating curve of the vacuum sintering process in this step is as follows: Figure 4 As shown, the following steps are included:

[0069] (1) Place the titanium alloy substrate with the sprayed working layer in a vacuum sintering furnace and evacuate to 10 -3Pa or lower to ensure that there is no oxygen or other gases affecting the coating quality during the sintering process.

[0070] (2) Initial low temperature stage: From room temperature to 500°C, the temperature is increased at a rate of 10°C / min and maintained at 500°C for 30 minutes. In the lower temperature range, the slow heating rate helps to gradually heat the substrate and coating to avoid thermal shock and stress concentration caused by rapid heating. This stage is mainly to eliminate moisture and volatile impurities on the surface of the material, while preparing for the intermediate temperature section.

[0071] (3) Intermediate temperature stage: from 500°C to 800°C, the temperature is increased at a rate of 10°C / min, and maintained at 800°C for 30 minutes. In the intermediate temperature range, the thermal stress inside the material is further released to ensure uniform temperature distribution. At the same time, it is also to promote the uniform diffusion of Ti and Ni elements in the titanium matrix and the nickel plating layer to form a TiNi phase. This stage is also to make full preparations for the final high-temperature sintering stage and gradually increase the temperature.

[0072] (4) High temperature sintering stage: from 800℃ to 1200~1300℃, the temperature is increased at a rate of 5℃ / min. In the high temperature range, the heating rate is further reduced to avoid thermal stress concentration caused by the difference in thermal expansion coefficient. After reaching the sintering temperature of 1200~1300℃, a 1~2 hour heat preservation treatment is carried out to allow the coating material to fully diffuse and combine to form a uniform and dense structure.

[0073] (5) Cooling stage: After vacuum sintering is completed, slowly cool to room temperature at a rate of 5°C / min to avoid thermal stress and cracks caused by rapid cooling. During the cooling process, nitrogen is introduced to normal pressure to prevent the coating from rapid oxidation in the air. Keep the nitrogen flow stable to ensure that the coating surface is not exposed to oxygen.

[0074] The vacuum sintering process with step-by-step heating, through slow heating rate and staged temperature control, the substrate and coating can gradually adapt to temperature changes, avoiding thermal stress concentration and material cracks caused by rapid heating. Especially in the low and medium temperature stages, slow heating helps to eliminate moisture and residual adhesive on the surface of the material, release the thermal stress inside the coating, and at the same time, in order to promote the uniform diffusion of Ti and Ni elements in the titanium substrate and nickel plating layer, the TiNi phase is formed. In the high-temperature sintering stage (1200-1300℃), the coating material can fully diffuse and combine to form a uniform and dense structure. At high temperature, the nickel plating layer diffuses with the metal atoms such as Ti, Ni, Co, Cr, Fe, and Mo in the coating material and titanium substrate to promote metallurgical bonding. This combination not only enhances the adhesion of the coating, but also improves the mechanical properties and high-temperature oxidation resistance of the coating. Especially in high-entropy alloy coatings, the diffusion and mixing of different elements help to form a stable multi-phase structure and improve the comprehensive performance of the material. At the same time, slow cooling can avoid thermal stress and microcracks caused by rapid cooling, and maintain the integrity and stability of the coating.

[0075] Example 1

[0076] Step 1: Substrate preparation and surface activation:

[0077] Prepare a TC11 titanium alloy substrate, immerse the titanium alloy substrate in anhydrous ethanol solution for ultrasonic cleaning, immerse the cleaned titanium alloy substrate in a mixed pickling solution of 30mL HF and 70mL HNO3 for 3 minutes for surface activation treatment, and then rinse thoroughly with deionized water and blow dry.

[0078] Step 2: Electroplating nickel layer:

[0079] Prepare nickel sulfate (NiSO 4 6H 2 O) 280g / L, nickel chloride (NiCl 2 6H 2 O) 60g / L, boric acid (H 3 BO 3 )40g / L plating solution. Adjust the pH of the plating solution to 4.3 and heat it to 55°C. Then put the titanium alloy substrate and the nickel anode into the plating tank respectively, and set the current density to 3A / dm 2 The electroplating time is 1 hour, and a nickel plating layer with a thickness of 30 μm is formed.

[0080] Step 3: Cold spraying of nano adhesive layer:

[0081] Prepare a nano adhesive, the chemical composition and its mass percentage are: polyvinyl alcohol 70%, plasticizer (glycerol) 7%, filler (ceramic nano Al 2 O 3The nano adhesive was sprayed on the surface of the electroplated nickel layer by cold spraying process, with a spraying pressure of 0.3 MPa, a nozzle diameter of 0.3 mm, a spraying distance of 15 cm, a speed of 100 mm / s, and a thickness of the adhesive layer of 10 μm.

[0082] Step 4: Cold spraying high entropy alloy base layer:

[0083] Prepare high entropy alloy powder, the chemical composition and its mass percentage are: carbon accounts for 0.1%, boron accounts for 1%, chromium accounts for 19%, nickel accounts for 21%, silicon accounts for 1%, molybdenum accounts for 8%, cobalt accounts for 22%, sulfur accounts for 0.005%, phosphorus accounts for 0.015%, and the balance is iron. Use cold spraying process to spray the high entropy alloy powder on the nano adhesive layer, with a spraying pressure of 2MPa, a nozzle diameter of 1mm, a spraying distance of 30cm, and a spraying speed of 200mm / s to form a base layer with a thickness of 200μm.

[0084] Step 5: Debonding and semi-melting-curing treatment:

[0085] Use an oxyacetylene flame spray gun to remove the adhesive from the base layer in step 4, flame temperature: 200°C, flame type: neutral flame (equal ratio of oxygen and acetylene), nozzle diameter: 1.0mm, distance between nozzle and coating surface: 10cm, scan the surface of the base layer for 5 seconds, and then use an oxyacetylene flame spray gun to semi-melt and solidify the base layer, flame temperature: 800°C, flame type: neutral flame (equal ratio of oxygen and acetylene), nozzle diameter: 1.5mm, distance between nozzle and coating surface: 20cm, scan the surface of the base layer for 10 seconds.

[0086] Step 6: Cold spraying high entropy alloy working layer layer by layer:

[0087] On the basis of the base layer, the nano adhesive and high entropy alloy powder are cold sprayed layer by layer to ensure that the single layer thickness is controlled at 200μm. In addition to the base layer, after each spraying, the coating is debonded and semi-melted-solidified using an oxyacetylene flame spray gun until the cyclic deposition reaches a working layer of 1mm.

[0088] Step 7: Vacuum sintering:

[0089] Place the cold sprayed working layer coating in a vacuum sintering furnace and evacuate to 10-3Pa. Use a step-by-step heating method, heating from room temperature to 500℃ at 10℃ / min, and keep at 500℃ for 30 minutes; heating from 500℃ to 800℃ at 10℃ / min, and keep at 800℃ for 30 minutes; heating from 800℃ to 1200℃ at 5℃ / min, and keep at 1200℃ for 1.5 hours. Slowly cool to room temperature at a rate of 5℃ / min. The coating is prepared and numbered Figure 5 and Figure 6 Coating #1 in.

[0090] Example 2

[0091] Step 1: Substrate preparation and surface activation:

[0092] Prepare a TC11 titanium alloy substrate, immerse the titanium alloy substrate in anhydrous ethanol solution for ultrasonic cleaning, immerse the cleaned titanium alloy substrate in a mixed pickling solution of 30mL HF and 70mL HNO3 for 3 minutes for surface activation treatment, and then rinse thoroughly with deionized water and blow dry.

[0093] Step 2: Electroplating nickel layer:

[0094] Prepare nickel sulfate (NiSO 4 6H 2 O) 280g / L, nickel chloride (NiCl 2 6H 2 O) 60g / L, boric acid (H 3 BO 3 )40g / L plating solution. Adjust the pH of the plating solution to 4.3 and heat it to 55°C. Then put the titanium alloy substrate and the nickel anode into the plating tank respectively, and set the current density to 3A / dm 2 The electroplating time is 1.5 hours, and a nickel plating layer with a thickness of 40 μm is formed.

[0095] Step 3: Cold spraying of nano adhesive layer:

[0096] Prepare a nano adhesive, the chemical composition and its mass percentage are: polyvinyl alcohol 70%, plasticizer (glycerol) 7%, filler (ceramic nano Al 2 O 3 The nano adhesive was sprayed on the surface of the electroplated nickel layer by cold spraying process, with a spraying pressure of 0.3 MPa, a nozzle diameter of 0.3 mm, a spraying distance of 15 cm, a speed of 100 mm / s, and a thickness of the adhesive layer of 10 μm.

[0097] Step 4: Cold spraying high entropy alloy base layer:

[0098] Prepare high entropy alloy powder, the chemical composition and its mass percentage are: carbon accounts for 0.1%, boron accounts for 1%, chromium accounts for 19%, nickel accounts for 21%, silicon accounts for 1%, molybdenum accounts for 8%, cobalt accounts for 22%, sulfur accounts for 0.005%, phosphorus accounts for 0.015%, and the balance is iron. Use cold spraying process to spray the high entropy alloy powder on the nano adhesive layer, with a spraying pressure of 2MPa, a nozzle diameter of 1mm, a spraying distance of 30cm, and a spraying speed of 200mm / s to form a base layer with a thickness of 200μm.

[0099] Step 5: Debonding and semi-melting-curing treatment:

[0100] Use an oxyacetylene flame spray gun to remove the adhesive from the base layer in step 4, flame temperature: 200°C, flame type: neutral flame (equal ratio of oxygen and acetylene), nozzle diameter: 1.0mm, distance between nozzle and coating surface: 10cm, scan the surface of the base layer for 5 seconds, and then use an oxyacetylene flame spray gun to semi-melt and solidify the base layer, flame temperature: 800°C, flame type: neutral flame (equal ratio of oxygen and acetylene), nozzle diameter: 1.5mm, distance between nozzle and coating surface: 20cm, scan the surface of the base layer for 10 seconds.

[0101] Step 6: Cold spraying high entropy alloy working layer layer by layer:

[0102] On the basis of the base layer, the nano adhesive and high entropy alloy powder are cold sprayed layer by layer to ensure that the single layer thickness is controlled at 200μm. In addition to the base layer, after each spraying, the coating is debonded and semi-melted-solidified using an oxyacetylene flame spray gun until the cyclic deposition reaches a working layer of 1mm.

[0103] Step 7: Vacuum sintering:

[0104] Place the cold sprayed working layer coating in a vacuum sintering furnace and evacuate to 10-3Pa. Use a step-by-step heating method, heating from room temperature to 500℃ at 10℃ / min, and keep at 500℃ for 30 minutes; heating from 500℃ to 800℃ at 10℃ / min, and keep at 800℃ for 30 minutes; heating from 800℃ to 1200℃ at 5℃ / min, and keep at 1200℃ for 1.5 hours. Slowly cool to room temperature at a rate of 5℃ / min. The coating is prepared and numbered Figure 5 and Figure 6 Coating #2 in.

[0105] Example 3

[0106] Step 1: Substrate preparation and surface activation:

[0107] Prepare a TC11 titanium alloy substrate, immerse the titanium alloy substrate in anhydrous ethanol solution for ultrasonic cleaning, immerse the cleaned titanium alloy substrate in a mixed pickling solution of 30mL HF and 70mL HNO3 for 3 minutes for surface activation treatment, and then rinse thoroughly with deionized water and blow dry.

[0108] Step 2: Electroplating nickel layer:

[0109] Prepare nickel sulfate (NiSO 4 6H 2 O) 280g / L, nickel chloride (NiCl2 6H 2 O) 60g / L, boric acid (H 3 BO 3 )40g / L plating solution. Adjust the pH of the plating solution to 4.3 and heat it to 55°C. Then put the titanium alloy substrate and the nickel anode into the plating tank respectively, and set the current density to 3A / dm 2 The electroplating time is 1 hour, and a nickel plating layer with a thickness of 40 μm is formed.

[0110] Step 3: Cold spraying of nano adhesive layer:

[0111] Prepare a nano adhesive, the chemical composition and its mass percentage are: polyvinyl alcohol 65%, plasticizer (glycerol) 7%, filler (ceramic nano Al 2 O 3 The nano adhesive was sprayed on the surface of the electroplated nickel layer by cold spraying process, with a spraying pressure of 0.3 MPa, a nozzle diameter of 0.3 mm, a spraying distance of 15 cm, a speed of 100 mm / s, and a thickness of the adhesive layer of 10 μm.

[0112] Step 4: Cold spraying high entropy alloy base layer:

[0113] Prepare high entropy alloy powder, the chemical composition and its mass percentage are: carbon accounts for 0.1%, boron accounts for 1%, chromium accounts for 19%, nickel accounts for 21%, silicon accounts for 1%, molybdenum accounts for 8%, cobalt accounts for 22%, sulfur accounts for 0.005%, phosphorus accounts for 0.015%, and the balance is iron. Use cold spraying process to spray the high entropy alloy powder on the nano adhesive layer, with a spraying pressure of 2MPa, a nozzle diameter of 1mm, a spraying distance of 30cm, and a spraying speed of 200mm / s to form a base layer with a thickness of 200μm.

[0114] Step 5: Debonding and semi-melting-curing treatment:

[0115] Use an oxyacetylene flame spray gun to remove the adhesive from the base layer in step 4, flame temperature: 200°C, flame type: neutral flame (equal ratio of oxygen and acetylene), nozzle diameter: 1.0mm, distance between nozzle and coating surface: 10cm, scan the surface of the base layer for 5 seconds, and then use an oxyacetylene flame spray gun to semi-melt and solidify the base layer, flame temperature: 800°C, flame type: neutral flame (equal ratio of oxygen and acetylene), nozzle diameter: 1.5mm, distance between nozzle and coating surface: 20cm, scan the surface of the base layer for 10 seconds.

[0116] Step 6: Cold spraying high entropy alloy working layer layer by layer:

[0117] On the basis of the base layer, the nano adhesive and high entropy alloy powder are cold sprayed layer by layer to ensure that the single layer thickness is controlled at 200μm. In addition to the base layer, after each spraying, the coating is debonded and semi-melted-solidified using an oxyacetylene flame spray gun until the cyclic deposition reaches a working layer of 1mm.

[0118] Step 7: Vacuum sintering:

[0119] Place the cold sprayed working layer coating in a vacuum sintering furnace and evacuate to 10-3Pa. Use a step-by-step heating method, heating from room temperature to 500℃ at 10℃ / min, and keep at 500℃ for 30 minutes; heating from 500℃ to 800℃ at 10℃ / min, and keep at 800℃ for 30 minutes; heating from 800℃ to 1200℃ at 5℃ / min, and keep at 1200℃ for 1.5 hours. Slowly cool to room temperature at a rate of 5℃ / min. The coating is prepared and numbered Figure 5 and Figure 6 Coating #3 in.

[0120] Comparative Example 1

[0121] Step 1: Substrate preparation and surface roughening:

[0122] A TC11 titanium alloy substrate was prepared, and the surface of the titanium alloy substrate was polished with 800# metallographic sandpaper to remove the surface oxide film. The titanium alloy substrate was immersed in anhydrous ethanol solution for ultrasonic cleaning and then dried.

[0123] Step 2: Cold spraying of nano adhesive layer:

[0124] Prepare a nano adhesive, whose chemical composition and mass percentage are: polyvinyl alcohol 80%, plasticizer (glycerol) 10%, deionized water 10%. Use cold spraying process to spray the nano adhesive on the surface of the electroplated nickel layer, spraying pressure 0.3MPa, nozzle diameter 0.3mm, spraying distance 15cm, speed 100mm / s, and the thickness of the adhesive layer is 10μm.

[0125] Step 3: Cold spraying high entropy alloy base layer:

[0126] Prepare high entropy alloy powder, the chemical composition and its mass percentage are: carbon accounts for 0.1%, boron accounts for 1%, chromium accounts for 19%, nickel accounts for 21%, silicon accounts for 1%, molybdenum accounts for 8%, cobalt accounts for 22%, sulfur accounts for 0.005%, phosphorus accounts for 0.015%, and the balance is iron. Use cold spraying process to spray the high entropy alloy powder on the nano adhesive layer, with a spraying pressure of 2MPa, a nozzle diameter of 1mm, a spraying distance of 30cm, and a spraying speed of 200mm / s to form a base layer with a thickness of 200μm.

[0127] Step 4: Debonding and semi-melting-curing treatment:

[0128] Use an oxyacetylene flame spray gun to remove the adhesive from the base layer in step 4, flame temperature: 200°C, flame type: neutral flame (equal ratio of oxygen and acetylene), nozzle diameter: 1.0mm, distance between nozzle and coating surface: 10cm, scan the surface of the base layer for 5 seconds, and then use an oxyacetylene flame spray gun to semi-melt and solidify the base layer, flame temperature: 800°C, flame type: neutral flame (equal ratio of oxygen and acetylene), nozzle diameter: 1.5mm, distance between nozzle and coating surface: 20cm, scan the surface of the base layer for 10 seconds.

[0129] Step 5: Cold spraying high entropy alloy working layer layer by layer:

[0130] On the basis of the base layer, the nano adhesive and high entropy alloy powder are cold sprayed layer by layer to ensure that the single layer thickness is controlled at 200μm. In addition to the base layer, after each spraying, the coating is debonded and semi-melted-solidified using an oxyacetylene flame spray gun until the cyclic deposition reaches a working layer of 1mm.

[0131] Step 6: Vacuum sintering:

[0132] The cold sprayed working layer coating is placed in a vacuum sintering furnace and evacuated to 10-3 Pa. The temperature is quickly raised to 1200℃, maintained at 1200℃ for 1.5 hours, and nitrogen is directly filled in for rapid cooling. The coating is prepared and numbered. Figure 5 and Figure 6 Coating #4 in.

[0133] The thickness and bonding strength of each coating in the above-mentioned embodiments and comparative examples are shown in Table 1. The thickness of coating 1# in the embodiment is 1.037mm, and the bonding strength between the substrate and the coating is 54MPa. The thickness of coating 2# in the embodiment is 1.071mm, and the bonding strength between the substrate and the coating is 59MPa. The thickness of coating 3# in the embodiment is 1.055mm, and the bonding strength between the substrate and the coating is 55MPa. The thickness of coating 4# in comparative example 1 is 0.973mm, and the bonding strength between the substrate and the coating is 32MPa. In contrast, in comparative example 1, the nickel layer was not electroplated during electroplating, resulting in a serious decrease in the bonding strength between the substrate and the coating. At the same time, the thickness of the electroplated nickel layer increases, which further alleviates the difference in thermal expansion coefficient and improves the adhesion of the coating. In addition, as Figure 5 As shown in the figure, the microhardness of coating 3# in the embodiment is greater than that of coatings 1# and 2#, due to the Al 2 O 3 The particle content (20%) is higher than that of coatings 1# and 2# (15%). This indicates that the Al content in the coating is 2 O 3 The particles can significantly improve the microhardness and wear resistance of the coating.

[0134] Table 1 Thickness of each coating and bonding strength between coating and substrate in Examples and Comparative Examples

[0135] Coating thickness(mm) Bonding strength between coating and substrate (MPa) Example 1# 1.037 54 Example 2# 1.071 59 Example 3# 1.055 55 Example 4# 0.973 32

[0136] Comparison of high temperature oxidation resistance of the coatings of Example 1, Example 2 and Example 3 with Comparative Example 1:

[0137] The coating samples prepared in Example 1, Example 2, Example 3 and Comparative Example 1 were subjected to a high temperature oxidation test at 900° C. for 5 hours in a muffle furnace. Figure 6 As shown, the CoCrFeNiMoBSi coating on the surface of TC11 titanium alloy exhibits good high-temperature oxidation resistance at 900°C. The coating 3# prepared in Example 3 is oxidized at 900°C for 5 hours, and the oxidation weight gain rate is the lowest. However, the oxidation weight gain rate of coating 4# prepared in Comparative Example 1 is the highest. One reason is that the titanium alloy substrate is not electroplated with nickel in Comparative Example 1. Due to the large difference in thermal expansion coefficient between the titanium alloy substrate and the high-entropy alloy coating, large thermal stress is generated at the interface, forming defects such as pores and microcracks, which reduces the high-temperature oxidation resistance of the coating. The second reason is that no ceramic nano-Al is added to the adhesive in the comparative example. 2 O 3 The particles promote the formation of pore defects in the coating and reduce the high-temperature oxidation resistance of the coating. Third, because the vacuum sintering process in Comparative Example 1 did not perform step-by-step heating and slow cooling, the elements in the coating diffused unevenly, and a large amount of brittle intermetallic compounds were formed at the interface. Rapid cooling caused the thermal stress inside the coating to concentrate and form thermal cracks, which reduced the high-temperature oxidation resistance of the coating.

[0138] In summary, the high temperature oxidation resistance of Example 1, Example 2 and Example 3 is significantly better than that of Comparative Example 1.

[0139] It must be explained that the present invention combines multiple processes and designs the composition of the gradient coating to prepare a gradient coating with excellent high temperature oxidation resistance and adhesion under the cold spray process, and each step is coordinated and continuous to achieve the high performance of the final coating. In order to facilitate the creative explanation, the principle of the entire process is continuously explained below.

[0140] like Figure 1 As shown, interface I is titanium alloy substrate / nickel plating layer, and interface II is nickel plating layer / high entropy alloy coating.

[0141] First, the electroplating of nickel on the surface of titanium alloy is mainly to provide a new substrate on the surface of titanium alloy to solve the problem of mismatch in thermal expansion coefficients between titanium alloy and high entropy alloy coating. However, the electroplating of nickel on the surface of titanium alloy only makes the plated metal in close contact with the surface of titanium alloy substrate through van der Waals force and electrostatic attraction. The bonding strength between them is low and must be improved through metallurgical bonding.

[0142] Therefore, an oxyacetylene flame spray gun is used for semi-melting-solidification treatment at 800°C. On the one hand, it promotes the diffusion of Ti atoms in the titanium matrix to the nickel-plated layer, and the diffusion of Ni atoms in the nickel-plated layer to the titanium matrix. At 800°C, the diffusion coefficients of Ti and Ni atoms are low, and the element diffusion rate is low, which prompts the formation of a preliminary Ti-Ni diffusion layer at interface I. On the other hand, the Co, Cr, Fe, Ni, and Mo atoms in the high-entropy alloy coating diffuse into the nickel-plated layer, and the Ni atoms in the nickel-plated layer diffuse into the high-entropy alloy coating. At 800°C, the diffusion coefficient of Ni atoms is larger than that of Co, Cr, Fe, Ti, and Mo, which promotes the formation of a diffusion layer rich in Ni-based alloy at interface II. At the same time, the Cr atoms in the high-entropy alloy coating are oxidized in the air to form trace amounts of Cr 2 O 3 Oxide, providing a heterogeneous nucleation core for the growth of grains in the subsequent vacuum sintering process, and the ceramic nano-Al doped in the binder 2 O 3 The particles work in the same way. However, the short-term diffusion of elements cannot form a connected and reliable diffusion layer.

[0143] Therefore, a vacuum sintering process with a step-by-step temperature increase is adopted.

[0144] The temperature was raised from room temperature to 500°C at a rate of 10°C / min and kept at 500°C for 30 minutes. At 500°C, the atomic diffusion coefficients of Ti, Ni, Co, Cr, Fe, and Mo are low, and slow diffusion is conducive to the uniform diffusion of the elements in the interface, avoiding the formation of Kirkendall holes and other defects due to uneven diffusion of elements in the early interface. At this stage, the elements in interface I and interface II are in the uniform diffusion stage.

[0145] The temperature was raised from 500°C to 800°C at 10°C / min and kept at this temperature for 30 minutes. At 800°C, the atomic diffusion coefficients of Ti, Ni, Co, Cr, Fe, and Mo increased, but were still relatively low. The uniform diffusion of each element was further promoted to enhance the metallurgical bonding performance of the interface. At this stage, according to the TiNi phase diagram, at 800°C, the Ni and Ti elements at interface I interacted to form a NiTi phase. At the same time, due to the increase in the diffusion rate of each element, the Ni element at interface II segregated to form a γ-Ni phase. Due to the slow diffusion effect of high entropy alloys, the Ni, Co, Cr, Fe, and Mo elements in the high entropy alloy coating interacted to form a solid solution with a single FCC phase structure.

[0146] The temperature was raised from 800°C to 1200°C at a rate of 5°C / min and maintained at 1200°C for 1.5 hours. From 800°C to 1200°C, the diffusion coefficients of atoms such as Ti, Ni, Co, Cr, Fe, and Mo increased significantly, and the element diffusion rate increased significantly, which promoted the full diffusion of each element at the interface and formed a uniform diffusion layer. At this stage, as the diffusion proceeded, a solid phase reaction occurred, and the atoms at the interface began to rearrange to form a stable new phase. The new phase gradually formed and grew at the interface, and the grains began to grow to form a uniform microstructure.

[0147] When the sintering temperature reaches 1200℃, the diffusion of Ni, Co, Cr, Fe, and Mo atoms in the high-entropy alloy coating intensifies, and the accumulation of dislocation and strain energy begins to promote the recrystallization process. The recrystallization process begins, and new grains nucleate and grow in high-energy areas (such as dislocation-intensive areas and grain boundaries). The new grains grow rapidly, gradually replacing the original deformed grains, and the microstructure inside the coating tends to be uniform, and the grains are refined. After the recrystallization is completed, the coating forms a uniform and fine grain structure.

[0148] The examples described in the present invention are merely descriptions of the preferred implementation modes of the present invention, and are not intended to limit the concept and scope of the present invention. Without departing from the design concept of the present invention, various modifications and improvements made to the technical solutions of the present invention by engineers and technicians in this field should all fall within the protection scope of the present invention.

Claims

1. A high temperature oxidation resistant gradient coating, Features: It includes a nickel plating layer, a nano adhesive layer and a working layer which are sequentially arranged from the inside to the outside; The chemical composition and mass percentage of the nickel plating layer are: nickel: 98-99%, sulfur: 0.01-0.05%, and the balance is other impurity elements; The chemical composition and mass percentage of the nano adhesive layer are: polyvinyl alcohol: 50-70%, plasticizer: 5-10%, ceramic nano Al 2 O 3 Particles: 10-20%, deionized water: 10-20%; The working layer comprises multiple high entropy alloy layers, and there is a nano adhesive between two adjacent high entropy alloy layers. The chemical composition and mass percentage of the high entropy alloy layer are: Carbon: 0.1-0.5%, boron: 1-1.3%, chromium: 19-21%, nickel: 21-24%, silicon: 1-1.5%, molybdenum: 8-10%, cobalt: 22-24%, sulfur: 0.005-0.015%, phosphorus: 0.015-0.045%, and the balance is iron and inevitable impurities.

2. A high temperature oxidation resistant gradient coating according to claim 1, Features: The thickness of the nickel plating layer is 30-50 μm.

3. A high temperature oxidation resistant gradient coating according to claim 1, Features: The thickness of the nano adhesive layer is 10 to 20 μm.

4. The high temperature oxidation resistant gradient coating according to claim 1, Features: The thickness of the high entropy alloy layer is 100-200 μm, and the thickness of the working layer is 1-1.2 mm.

5. A method for preparing the high temperature oxidation resistant gradient coating according to any one of claims 1 to 4, It is characterized in that The following steps are involved:

1. Prepare the titanium alloy substrate and perform ultrasonic cleaning and pickling activation treatment; 2. electroplating a nickel layer on the titanium alloy substrate to form a nickel-plated layer; 3. Spraying a nano adhesive layer on the nickel-plated layer using a cold spraying process; Fourth, a cold spraying process is used to spray high entropy alloy powder on the nano adhesive layer to form a base layer; 5. Use an oxyacetylene flame spray gun to remove the adhesive and semi-melt-solidify the primer layer; 6. On the basis of the base layer, cold spray the nano adhesive and high entropy alloy powder layer by layer until a working layer is formed; 7. Vacuum sintering the cold sprayed working layer; 8. After the vacuum sintering is completed, slowly cool to room temperature to complete the coating preparation.

6. The method for preparing a high temperature oxidation resistant gradient coating according to claim 5, Features: In the step 2, the nickel-plated layer is prepared by: (1) Adding nickel sulfate, nickel chloride and boric acid into the electroplating tank, adjusting the pH value of the electroplating solution to 4 to 4.5, and heating the electroplating solution to 50 to 60° C.; (2) Use high-purity nickel as the anode material for electroplating, with a current density of 2 to 4 A / dm 2 The electroplating time is 1 to 2 hours.

7. The method for preparing a high temperature oxidation resistant gradient coating according to claim 5, Features: In the step three, the spraying pressure is 0.2-0.4 MPa, the nozzle diameter is 0.2-0.4 mm, the spraying distance is 10-20 cm, and the spraying speed is 100-200 mm / s.

8. The method for preparing a high temperature oxidation resistant gradient coating according to claim 5, Features: In the step 4, the spraying pressure is 1.5-3 MPa, the nozzle diameter is 0.8-1.2 mm, the spraying distance is 25-35 cm, and the spraying speed is 150-300 mm / s.

9. The method for preparing a high temperature oxidation resistant gradient coating according to claim 5, Features: In the step five, when the adhesive removal treatment is performed, the flame temperature is 200-300°C, the nozzle diameter is 1.0-1.5 mm, the distance between the nozzle and the surface of the base layer is 10-15 cm, and each heating is 5-10 seconds; when the semi-melting-curing treatment is performed, the flame temperature is 600-800°C, the nozzle diameter is 1.0-1.5 mm, the distance between the nozzle and the surface of the base layer is 10-20 cm, and each heating is 5-10 seconds.

10. The method for preparing a high temperature oxidation resistant gradient coating according to claim 5, Features: In step 7, a step-by-step heating method is used, specifically: (1) Heating from room temperature to 500°C at a rate of 10°C / min and keeping at 500°C for 30 min; (2) heating from 500°C to 800°C at a rate of 10°C / min and maintaining at 800°C for 30 min; (3) Raise the temperature from 800°C to 1200-1300°C at a rate of 5°C / min and keep at 1200-1300°C for 1-2 hours.

Citation Information

Patent Citations

  • Wear-resistant blade as well as preparation method and application thereof

    CN114990465A

  • Self-fluxing high-entropy alloy powder and preparation and application methods thereof

    CN115094294A

  • Anti-radiation high-entropy alloy / ceramic multilayer film and preparation method thereof

    CN115386839A

  • Wear-resistant blade, and preparation method therefor and use thereof

    WO2023236728A1

Cited By

  • A high-entropy alloy composite coating on titanium alloy surface and its preparation method

    CN122727796A